9(6x-7)=49

Simple and best practice solution for 9(6x-7)=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(6x-7)=49 equation:


Simplifying
9(6x + -7) = 49

Reorder the terms:
9(-7 + 6x) = 49
(-7 * 9 + 6x * 9) = 49
(-63 + 54x) = 49

Solving
-63 + 54x = 49

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '63' to each side of the equation.
-63 + 63 + 54x = 49 + 63

Combine like terms: -63 + 63 = 0
0 + 54x = 49 + 63
54x = 49 + 63

Combine like terms: 49 + 63 = 112
54x = 112

Divide each side by '54'.
x = 2.074074074

Simplifying
x = 2.074074074

See similar equations:

| (x+3)(y-7)=960 | | 0.83x-2=0.75 | | 2(y+2)=3 | | mx-1=x^2-5x+4 | | 112=17.5w+7 | | P=162x-81x^2 | | 2(5x-5)=(7y-9) | | 5-4(3+5v)+8= | | 0.375x+4=0.66 | | -6+3k=4k-8 | | 6x-18=2x+12 | | 6(4v+2)=36 | | 1/9m-3=0 | | 5x+7y-4z=31 | | -x-11/3=21 | | (2x+40)+(5x+12)= | | w-4w-32=0 | | 4t=21 | | 2p^2+2p-9=0 | | 2x-y-1=o | | 0.045=x | | 0.5x-3=0.8 | | 2(x+2)-6=5x+1 | | 9k-2k+3k-6k=12 | | x-75/7.5=y | | 2(2w+7)=2w+7 | | y=.33(9x-18) | | 2a+7a+13a+(-5a)-15a-4=-10 | | 6=1/12x | | 3x-14/4=x-8 | | 5x+35=13x-5 | | 6x=12.24 |

Equations solver categories